2019
DOI: 10.18844/prosoc.v6i1.4154
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review on psychosocial factors of adolescents' online self-disclosure

Abstract: It is said that nowadays online self-disclosure plays an essential role in adolescents’ development and it gains a lot of attention of today’s researchers. However, it is still unclear what are the particular psychosocial factors related to adolescents’ online self-disclosure as in general researchers analyse specific elements (e.g., narcissism, privacy concerns), related to the aims of their study. Thus, the systematic literature review has been organised on purpose to find out what are the most significant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is essential to mention that the majority of studies, analysing online photo disclosure, are based on young adults (mostly university or college students) (Paluckaitė & Žardeckaitė-Matulaitienė, 2019). Thus, the analysis of adolescents' risky photo disclosure online, is still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to mention that the majority of studies, analysing online photo disclosure, are based on young adults (mostly university or college students) (Paluckaitė & Žardeckaitė-Matulaitienė, 2019). Thus, the analysis of adolescents' risky photo disclosure online, is still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Shea, Fredericksen, Pickett, Pelz, and Swan [31] found that the quality and quantity of interactions were important for students' satisfaction in online classes. Paluckaite, and Zardeckaite-Matulaitiene [26], Hrastinski [18] suggests the online learning theory as online participation and is supported by "all kinds of engaging activities that are synonymous and asynchronous with speech or writing, that online learner participation is a complex process and maintains relationships with others, supported by physical and psychological means".…”
Section: Introductionmentioning
confidence: 99%
“…There are many factors that motivate teachers to teach lessons online or increase their satisfaction via online lessons. According to the results of the researches, making flexible programs, applying new teaching methods and techniques, learning new technologies, natural curiosity, sharing information in different ways, and professional development [19,32,35,26] is one of the factors that motivate teachers to teach online. In addition, the online teaching experience affects teachers' motivation and satisfaction with online teaching.…”
Section: Introductionmentioning
confidence: 99%